HGF/c-MET抑制剂治疗非小细胞肺癌的研究进展 (Zhongguo Fei Ai Za Zhi, 2015)
Molecular targeted therapy has become more and more important in the treatment of non-small cell lung cancer (NSCLC). HGF/c-MET plays the pivotal role in the growth, development and tolerance to epidermal growth factor receptor tyrosine kinase inhibitor of NSCLC. Moreover it has become another heat point in the molecular targeted therapy of NSCLC. c-MET amplification or high expression was deemed to another significant gene modification beyond EGFR and ALK. In the preclinical studies, HGF/c-MET inhibitors have showed the promising anti-tumor effect. Recently, some phase Ⅱ/Ⅲ clinical trials have proved that these inhibitors could improve the survival of patients with NSCLC. Hence we performed this review to elaborate the research progress of c-MET inhibitor in the treatment of NSCLC.